Dissecting the Function of MADS-Box Transcription Factors in Orchid Reproductive Development - Teo, Zhi Wei Norman; Zhou, Wei; Shen, Lisha (Frontiers in Plant Science, 2019)
The orchid family (Orchidaceae) represents the second largest family of flowering plants, having more than 900 genera and 27,000 species in almost all parts of the world. Orchids have evolved in many intriguing ways in order to survive extreme weather conditions, acquire nutrients and attract pollinators for reproduction. The MADS-box family of transcriptional factors have been shown to be involved in the regulation of many developmental processes and environmental responses in eukaryotes. Several findings in different orchid species have elucidated that MADS-box transcription factors play critical roles in the orchid growth and development. An in-depth understanding of their ecological adaptation will help to generate more interest among breeders and produce novel varieties for the floriculture industry. In this review, we summarize recent findings of MADS-box transcription factors regulating various growth and development processes in orchids, in particularly, the floral transition and floral patterning. We also discuss the prospects for future research in light of new genome resources and gene editing technologies that could be applied in orchid research and breeding.